Someone can demonstrate me why(adsbygoogle = window.adsbygoogle || []).push({});

##Re(z) = \frac{1}{2} \left ( z+\bar{z} \right )##

##Im(z) = \frac{1}{2i} \left ( z-\bar{z} \right )##

##Abs(z)=\sqrt{z\bar{z}}##

##Arg(z)=-i ln\left ( \frac{z}{\sqrt{z\bar{z}}} \right )##

?

2# Is correct to affirm that

##Arg(z)=-i ln\left (\sqrt{\frac{z}{\bar{z}}} \right)##

?

**Physics Forums - The Fusion of Science and Community**

# Demonstration for Re(z), Im(z), Abs(z) and Arg(z)

Have something to add?

- Similar discussions for: Demonstration for Re(z), Im(z), Abs(z) and Arg(z)

Loading...

**Physics Forums - The Fusion of Science and Community**